VER CON OTROS OJOS: INDAGACIÓN CUALITATIVA Y EXPERIENCIAS CONTEXTUADAS EN LA FORMACIÓN DE PROFESIONALES EN PSICOLOGÍA - Chavarría González, María Celina (2012)
A theoretical and practical involvement of 20 students from a Seminar Topics "Hermeneutics and contextualized intervention in child counseling," and we consider legitimate. This document represents a variant of systematization that was written exclusively for consultation technical team Children's Center Laboratory at the University of Costa Rica (CIL), one of three documents on the inquiry feedback on hermeneutics. It says the array of circumstances that led to this practice as well as the dimensions they discovered and how the issues were disputed, from a contextual, historical-critical and totalizing. We discuss processes, transformations and deadlocks on two interwoven themes: (1) the perception of and contribution to a children's center university, and (2) the effects of participation on vocational training. It also stresses the need for transdisciplinary work, not only interdisciplinary, in all dimensions, conscious and unconscious experience for children fostered. It tries to transcend the emerging vision of Laing complaint consistent with that vision. Finally, it makes visible the relevance of training and decoding phenomenological observation of the everyday in professional training in psychology.